2021
DOI: 10.4236/ce.2021.125073
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity of Preschool Children in COVID-19 Pandemic: Focusing on Activity Content and Exercise Intensity during Childcare

Abstract: The present study examined the relationship between children's activities at a nursery school and the amount of physical activity in the COVID-19 pandemic and obtained primary data to promote future childcare activities. Healthy preschool children aged 3 -5 (N = 21) participated in the survey. Children wore an activity tracker (Polar, A360) on the wrist of the non-dominant hand for three hours in the morning on five days, just after the state of emergency was lifted. The measurements included "activity time", … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The spread of the novel Coronavirus infection and the prolonged and severe epidemic due to the emergence of mutant strains of the virus have significantly reduced children's opportunities for physical activity, which has raised concerns about their health. Hashimoto et al (2021) investigated Japanese preschool children's physical activity in 2020, immediately after lifting Japan's emergency declaration and COVID-19 preventive measures. The study indicated that children had not been physically active for the duration recommended by MEXT (Hashimoto et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The spread of the novel Coronavirus infection and the prolonged and severe epidemic due to the emergence of mutant strains of the virus have significantly reduced children's opportunities for physical activity, which has raised concerns about their health. Hashimoto et al (2021) investigated Japanese preschool children's physical activity in 2020, immediately after lifting Japan's emergency declaration and COVID-19 preventive measures. The study indicated that children had not been physically active for the duration recommended by MEXT (Hashimoto et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Hashimoto et al (2021) investigated Japanese preschool children's physical activity in 2020, immediately after lifting Japan's emergency declaration and COVID-19 preventive measures. The study indicated that children had not been physically active for the duration recommended by MEXT (Hashimoto et al, 2021). Hashimoto et al (2021) emphasized the situation in which activities of preschool children have been greatly restricted in daycare to cope with unusual situations and lifestyle changes.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations